A historical perspective and prospects of biomedical research on parasitic diseases - SIMÕES-BARBOSA, Augusto; SIMÕES BARBOSA, Constança; SIMÕES BARBOSA, Frederico (Revista do Instituto de Medicina Tropical de São Paulo, 2001)
We all hope that biotechnology will answer some social and economical unavoidable requirements of the modern life. It is necessary to improve agriculture production, food abundance and health quality in a sustainable development. It is indeed a hard task to keep the progress on taking into account the rational use of genetic resources and the conservation of biodiversity. In this context, a historical perspective and prospects of the biomedical research on parasitic diseases is described in a view of three generations of investigators. This work begins with a picture of the scientific progress on biomedical research and human health over the last centuries. This black-and-white picture is painted by dissecting current advancements of molecular biology and modern genetics, which are outlined at the meaning of prospecting achievements in health science for this new millenium.